2018
DOI: 10.1103/physreva.98.012131
|View full text |Cite
|
Sign up to set email alerts
|

Zero-temperature limit of thermodynamic quantum master equations

Abstract: We investigate the zero-temperature limit of thermodynamic quantum master equations that govern the time evolution of density matrices for dissipative quantum systems. The quantum master equations for T = 0 and for T > 0 possess completely different structures: (i) the equation for T = 0 is linear in the deviation from the ground-state density matrix, whereas the equation for T > 0, in general, is seriously nonlinear, and (ii) the Gibbs state is obtained as the steady-state solution of the nonlinear equation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…We choose f α (u) = f α constant, thus fulfilling such condition. In [40] it was shown that for a single two-level system described by H free = ωσ z , the rate f (u) can be chosen as exp(2uω/k B T ) if Q = σ + . The same reasoning was later on extended to a multi-mode bosonic field with Q k = a k [46].…”
Section: The Open Xxz Generic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We choose f α (u) = f α constant, thus fulfilling such condition. In [40] it was shown that for a single two-level system described by H free = ωσ z , the rate f (u) can be chosen as exp(2uω/k B T ) if Q = σ + . The same reasoning was later on extended to a multi-mode bosonic field with Q k = a k [46].…”
Section: The Open Xxz Generic Modelmentioning
confidence: 99%
“…While the reversible part is associated to the standard commutator of the density matrix with the system's Hamiltonian, the irreversible part leads to a term that is nonlinear in the density matrix but guarantees thermodynamic consistency and correct steady-state properties. This master equation was successfully applied to traditional open system scenarios, such as spontaneous decay of a two-level atom and the Caldeira-Legget model where numerical solutions were found by using deterministic integration methods for nonlinear equations as well as adaptations of stochastic unraveling [36][37][38][39][40]. Here, for the first time, we apply this framework to the study of dissipation in a many-body system, that is, and open spin chain described by the XXZ model.…”
Section: Introductionmentioning
confidence: 99%